Neuromuscular Fatigue Induced by a Mixed Martial Art Training Protocol - Giboin, Louis-Solal; Gruber, Markus (My University, 2022)
Giboin, L-S and Gruber, M. Neuromuscular fatigue induced by a mixed martial art training protocol. J Strength Cond Res XX(X): 000-000, 2019-Mixed martial arts (MMA) is a full-contact sport whose popularity and professionalism are rapidly growing. However, the specific physiological demands of this sport have been only scarcely studied so far, and especially the amount or type of neuromuscular fatigue induced by an MMA bout remains completely unknown. We estimated neuromuscular fatigue of knee extensors muscles during and after an MMA training protocol designed to simulate the physiological demands of MMA competition in competitive practitioners (n = 9) with isometric maximal voluntary force (MVF), potentiated muscle twitch at rest (Ptw), and voluntary activation (VA). Bayesian linear mixed models showed that the training protocol induced a reduction of MVF, Ptw, and VA. Although the largest reduction across time of VA was smaller than the largest reduction of Ptw, an effect of VA, but not of Ptw, was found on MVF variation. The training protocol induced neuromuscular fatigue, with a larger peripheral (Ptw) than central component (VA). However, despite the large decrease in Ptw, force production capacity was related only to VA, indicating that central control might play an important role in the compensation of the peripheral fatigue components estimated with Ptw. This central compensation can most probably prevent a too large loss of muscle force during the training protocol.
Keywords: MMA, central fatigue, peripheral fatigue, muscle fatigue, psychoneurophysiology, fight sport; 796